2015
DOI: 10.1016/j.chom.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Plasmodium falciparum Merozoite Surface Protein MSP1 Activates a Spectrin-Binding Function Enabling Parasite Egress from RBCs

Abstract: SummaryThe malaria parasite Plasmodium falciparum replicates within erythrocytes, producing progeny merozoites that are released from infected cells via a poorly understood process called egress. The most abundant merozoite surface protein, MSP1, is synthesized as a large precursor that undergoes proteolytic maturation by the parasite protease SUB1 just prior to egress. The function of MSP1 and its processing are unknown. Here we show that SUB1-mediated processing of MSP1 is important for parasite viability. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
217
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(235 citation statements)
references
References 55 publications
17
217
1
Order By: Relevance
“…Examination by electron tomography showed that the parasites in the C1-treated preparation fell into three broad groups: those in which segmentation (merozoite budding) had not begun (as indicated by a single multinucleated parasite, with a single membrane underlying the PVM), those at a stage of partial segmentation (in which the daughter merozoites are partially separated but still attached), and those (the majority) in which segmentation was complete, producing fully separated daughter merozoites. Importantly, all of the C1-blocked schizonts examined displayed an intact PVM, in accord with previous evidence that PKG inhibitors potently stall egress at a stage before rounding up and PVM rupture (10,14,28,41). Consistent with this, in all partially segmented schizonts we observed a clear contrast difference between the material in the vacuole and the material in the blood cell cytosol, with the red cell cytosol displaying a darker, more electron-dense appearance than the contents of the PV (Fig.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Examination by electron tomography showed that the parasites in the C1-treated preparation fell into three broad groups: those in which segmentation (merozoite budding) had not begun (as indicated by a single multinucleated parasite, with a single membrane underlying the PVM), those at a stage of partial segmentation (in which the daughter merozoites are partially separated but still attached), and those (the majority) in which segmentation was complete, producing fully separated daughter merozoites. Importantly, all of the C1-blocked schizonts examined displayed an intact PVM, in accord with previous evidence that PKG inhibitors potently stall egress at a stage before rounding up and PVM rupture (10,14,28,41). Consistent with this, in all partially segmented schizonts we observed a clear contrast difference between the material in the vacuole and the material in the blood cell cytosol, with the red cell cytosol displaying a darker, more electron-dense appearance than the contents of the PV (Fig.…”
Section: Resultssupporting
confidence: 77%
“…The selective PKG inhibitors compound 1 (C1) and compound 2 (C2) reversibly inhibit egress before the rounding up stage (10,14,28,41). In contrast, treatment with the broad-spectrum cysteine protease inhibitor E64 allows PVM rupture but selectively prevents erythrocyte membrane rupture, resulting in merozoites trapped in the blood cell after rupture of the PVM (30,42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that blocking processing of MSP1 blocks egress, where unprocessed MSP1 is not able to bind to spectrin and is subsequently unable to destabilize the erythrocyte cytoskeleton for egress (46). It thus appears that the secondary processing of MSP1 is quite sensitive to interactions of the complex with antibodies during schizogony and also the egress of parasites for invasion, revealing at least two possible mechanisms for interference in parasite growth.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant MSP on the parasite surface is MSP1, and it plays an essential role for parasite survival (1). Recent work has shown that the processing of MSP1 not only produces mature MSP1 fragments important for parasite viability but also appears to be important for parasite egress (46). Although the precise role of MSP1 during invasion has not been described, it is known that processed MSP1 binds to multiple peripheral merozoite surface proteins to form large macromolecular structures on the parasite (16,17,47).…”
Section: Discussionmentioning
confidence: 99%